Meaning and urban representation in the instrumental tango of the 21s century. The album Soundtrack Buenos Aires by Astillero & String Orchestra (Revista Argentina de Musicología, 2021)
Astillero, an influential contemporary tango sextet, released its third album in 2013 with a string orchestra. The album unfolds an inseparable sonic narrative of associations with Buenos Aires through instrumental pieces as if they were the city’s soundtrack. This listening experience reveals not only the iconicity of specific gestures and the hybrid nature of its musical resources, but also the dark fervor of modernity, the echoes of the past, and the vivacious present of Buenos Aires charged with social and cultural connotations during the 21st-century where the resurgence of tango establishes.In this article, I explore some concepts about the relationships between popular music, city (or urban places), and identity, trying to hermeneutically define how Soundtrack Buenos Aires develops its expressive strategies of urban signification and representation. From the analysis of the musical languages that intertwine with this critical apparatus, I establish three types of procedures that I call “mirages”, “reflections”, and “intersections”, three methodological approaches that I traverse through the compositions of this album.
Keywords: 21st-century instrumental tango; Astillero tango sextet; Buenos Aires; Music and the city; Musical analysis